Tagung der ICES Arbeitsgruppe über die Kabeljaubestände bei Ostgrönland - Schumacher, A. (1986)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010